Thermodynamic preliminary design of civil turbofans and variable geometry implementation - Kyritsis, V. E. (Cranfield University, 2006)
Implementation of Variable Geometry during the off-design operation of an aero gas turbine engine may cause deviations for restricted engine parameters when fight envelope requirements are met. A method to optimize the thermodynamic cycle of a engine with respect to fuel burn, while meeting a variety of airframe or technological restrictions at the three major operating points of the fight envelope, namely the Top of Climb, End of Runway and mid-cruise points is developed. Purpose is the comparison of engines on a common basis. The method is implemented and performance benefits are identified in a variety of studies, such as: o the theoretically infinite Variable Geometry in turbomachinery components o reduction of the turbine coolant fraction during cruise for long range civil fights o optimal variable nozzle geometry implementation during steady state and transient operation Core of the optimization procedure is a zero-dimensional engine arithmetic solver developed by the author from scratch for a 3-spool and 2-spool engine configuration. The solver utilizes real gas properties and an approximate dimensionless enthalpy rise profile at the fan exit for the separate modeling of the fan tip and hub region. Purpose for the development of the new code has been a common arithmetic treatment for steady-state and transient calculations within the same engine solver, which is thoroughly described.